ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Hendra Bayu Sulistya, 0725030040; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
This research purpose to research effect deviden payot ratio,profitability, manajerial ownership, size company to firm value.Population of this research is manufacture company who listed in Indonesia stock exchange from 2009 until 2011. To get sampel for this research the writer use purposive sampling and get 20 company sampel to researching. Than the writer use multiple regression model to explain effect variables.The result show that deviden payout ratio effect firm value positif with signification, that mean more bigger deviden payout ratio more bigger firm value. Other variable like profitability, manajerial ownership, and size company can not give effect for firm valur significanl.Keywords: Firm value, Deviden Payout Ratio,Profitability,Manajerial Ownership,Size Company, Annual Report